Preliminary estimates of regolith generation and mobility in the Susquehanna Shale Hills Critical Zone Observatory, Pennsylvania, using meteoric 10Be - West,N; Kirby,E; Bierman,P; Rood,D (Applied Geochemistry, 2011)
This study seeks to quantify the rate and timing of regolith generation in the Critical Zone at the Susquehanna Shale Hills Critical Zone Observatory (SSHO). Meteoric 10Be depth profiles were determined using measurements from 30 hillslope soil and bedrock core samples in an effort to constrain 10Be inventories. The SSHO is located in the temperate climate zone of central Pennsylvania and comprises a first-order watershed developed entirely on a Fe-rich, organic-poor, Silurian-aged shale. Two major perturbations to the landscape have occurred at SSHO in the geologically recent past, including significant and sustained periglacial activity until after the retreat of the Laurentide ice sheet (~21ka) and deforestation during early colonial land-use. Bulk soil samples (n=16) were collected at three locations along a planar hillslope on the southern ridge of the catchment, representing the ridge top, mid-slope and valley floor. Rock chip samples (n=14) were also collected from a 24m deep core drilled into the northern ridge top. All meteoric 10Be concentration profiles show a declining trend with depth, with most of the 10Be retained in the uppermost decimeters of the soil. Meteoric 10Be inventories are higher at the mid-slope and valley floor sample sites, at 3.71±0.02×1010at/cm2 and 3.69±0.02×1010at/cm2, than at the ridge top site (1.90±0.01×1010at/cm2). The 10Be inventory at the convex ridge top site implies a minimum residence time of ~10.6ka, or if erosion is steady, an erosion rate of 19.4±0.2m/My. © 2011 Elsevier Ltd.